2013
DOI: 10.4236/jbnb.2013.43030
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond-Based Tests Systems for Biochemical Determination of Glucose and Cholesterol

Abstract: Model test-systems for biochemical determination of glucose and cholesterol are designed by covalent coupling of enzymes to the surface of modified nanodiamonds (MND). In both cases after immobilization on MND the enzymes exhibit activity and catalyze the formation of a colored product in the chain of successive enzymatic reactions of oxidative azocoupling ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…In our previous studies, we showed that MNDs can be used to construct systems for biochemical diagnostics and targeted delivery of drugs and new antibacterial preparations [29][30][31]. The MND-enzyme systems were used in biochemical assays of physiologically significant analytes [29].…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we showed that MNDs can be used to construct systems for biochemical diagnostics and targeted delivery of drugs and new antibacterial preparations [29][30][31]. The MND-enzyme systems were used in biochemical assays of physiologically significant analytes [29].…”
Section: Research Articlementioning
confidence: 99%
“…In our previous studies, we showed that MNDs can be used to construct systems for biochemical diagnostics and targeted delivery of drugs and new antibacterial preparations [29][30][31]. The MND-enzyme systems were used in biochemical assays of physiologically significant analytes [29]. The immobilization of the sensing element (nanoparticle-biomarker conjugate) on a solid support can be adapted and advanced the experimental indicator system for clinical analytical applications.…”
Section: Research Articlementioning
confidence: 99%
“…This opens prospects for the application of these nanoparticles for the separation and purification of biomolecules [13] [14] [15], immobilization and neutralization of toxins (e.g. mycotoxins) [16] [17], and creation of new systems for biochemical diagnosis [18] and new drug delivery systems [19].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we demonstrated the applicability of mod ified nanodiamonds (MNDs) obtained by detonation synthesis for separation and purification of proteins [1,2], design of systems for targeted delivery of biolog ically active compounds [3], and biochemical diagno sis of physiologically important compounds [4,5]. Further in vitro studies have shown the possibility of adsorption on MND particles of a number of protein and nonprotein components of human blood serum [6].…”
mentioning
confidence: 99%